Perceptions and Language Learning Strategies of Chinese Students: A Case Study of Chiang Rai Rajabhat University (CRRU) - Natthaphon Santhi; Sirikanya Dawilai; Bhudtree Wetpichetkosol (Fa Nuea Journal, 2022)
This study aimed to explore the Chinese students’ perceptions towards studying at Chiang Rai Rajabhat University (CRRU) and to survey their language learning strategies. The study totally recruited 80 third- and fourth-year Chinese students majoring in Thai Language and Culture Program from Faculty of Humanities at Chiang Rai Rajabhat University(CRRU) in the academic year 2019. The questionnaire surveying perceptions and language learning strategies was developed for data collection. The data was calculated for mean and standard deviation.The results revealed that the Chinese students’ perceptions towards learning at CRRU, in descending order, were learning environment and facilities, teaching and learning process, family supports and socio-cultural factors at the mean scores of 4.166 (S.D.=0.67), 4.05 (S.D.=0.75), 4.06 (S.D.=0.74). The Chinese students’ learning strategy choices, in descending order, were socio-affective strategies, metacognitive strategies, and cognitive strategies at the mean scores of 4.123 (S.D.=0.68), 4.065 (S.D.=0.71), and 3.968 (S.D.=0.73).